Adjuvant trastuzumab without chemotherapy for treating early HER2-positive breast cancer in older patients: A propensity score-adjusted analysis of a prospective cohort study. (December 2022) - Sawaki, Masataka; Taira, Naruto; Uemura, Yukari; Saito, Tsuyoshi; Baba, Shinichi; Kobayashi, Kokoro; Kawashima, Hiroaki; Tsuneizumi, Michiko; Sagawa, Noriko; Bando, Hiroko; Takahashi, Masato; Yamaguchi, Miki; et al.
Abstract: Purpose: To gauge the effects of treatment practices on prognosis for older patients with HER2-positive early breast cancer, particularly to determine whether adjuvant trastuzumab alone can offer benefit over no adjuvant therapy. This is a prospective cohort study which accompanies the RESPECT that is a randomized-controlled trial (RCT). Methods: Patients who declined the RCT were treated based on the physician's discretion. We studied the 1) trastuzumab-plus-chemotherapy group, 2) trastuzumab-monotherapy group, and 3) non-trastuzumab group (no therapy or anticancer therapy without trastuzumab). The primary endpoint was disease-free survival (DFS), which was compared using the propensity-score method. Relapse-free survival (RFS) and health-related quality of life (HRQoL) were assessed. Results: We enrolled 123 patients aged over 70 years (median: 74.5). Treatment categories were: trastuzumab-plus-chemotherapy group (n = 36, 30%), trastuzumab-monotherapy group (n = 52, 43%), and non-trastuzumab group (n = 32, 27%). The 3-year DFS was 96.7% in trastuzumab-plus-chemotherapy group, 89.2% in trastuzumab-monotherapy group, and 82.5% in non-trastuzumab group. DFS in non-trastuzumab group was lower than in trastuzumab-plus-chemotherapy and trastuzumab-monotherapy groups (propensity-adjusted hazard ratio; HR: 3.29; 95% CI: 1.15–9.39; P = 0.026). The RFS in non-trastuzumab group was lower than in trastuzumab-plus-chemotherapy and trastuzumab-monotherapy groups (propensity-adjusted HR = 7.80; 95% CI: 2.32–26.2, P < 0.0001). There were no significant intergroup differences in the proportions of patients showing HRQoL deterioration at 36 months (P = 0.717). Conclusion: Trastuzumab-treated patients had better prognoses than patients not treated with trastuzumab without deterioration of HRQoL. Trastuzumab monotherapy could be considered for older patients who reject chemotherapy. Highlights: There is less known about the efficacy of trastuzumab alone, although it avoids toxicity, especially in older patients. It is currently unknown whether adjuvant trastuzumab therapy alone can offer a benefit over no adjuvant therapy. Here, for the first time, we added an implication to this issue with propensity-adjustment analysis in a prospective study. We found that trastuzumab-treated patients had better prognoses than patients not treated with trastuzumab. Although trastuzumab plus chemotherapy remains a standard of care, trastuzumab can be considered for selected older patients.